Distribution and abundance of soil bacteria in the vicinity of Syowa Station in Antarctica, with special reference to habitat conditions - Yamanaka,Mitsuo; Kagawa,Hisanori (1984)
P(論文) The distribution of soil bacteria was investigated on twelve soil samples collected from ice-free areas near Syowa Station in Antarctica, with special reference to the environmental conditions. The total number of bacteria in samples from the various sites ranged widely from approximately (10)^2 to (10)^7 per gram soil. Although the environmental conditions of the twelve sampling points differed from each other, two interesting trends were observed between the bacteria flora and their habitats. (1) In general, the abundance of soil bacteria was higher in the surface soil which was covered with macroscopic plant community than that in the exposed soil. (2) The total number of bacteria, except for a few soil samples near Syowa Station, seems to be controlled by soil carbon (organic matter), which differed from the findings of other workers on the soils of the Dry Valleys area, Victoria Land, where the shortage of water limits life. departmental bulletin paper